FACTORS AFFECTING INTRAOCULAR BIOAVAILABILITY OF DRUGS - DESAI, MIRA; KAPADIA, JIGAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Ophthalmic drug delivery remains a significant challenge to the clinicians. A number of anatomic and physiological barriers restrict the entry of drug inside the ocular tissues, especially in the posterior segment of eye. The present review discusses various ocular barriers and drug factors which influence the ophthalmic drug delivery. Furthermore, recent advances in ophthalmic drug formulations attempted to overcome these barriers have been explored.